2018
DOI: 10.1177/1745499918791362
|View full text |Cite
|
Sign up to set email alerts
|

International Student Experiences in Non-Native-English-Speaking Countries: Postgraduate Motivations and Realities from Finland

Abstract: Globally, international student recruitment has become one of the prominent topics of higher education. In addition to the leading native-speaking English world, several non-native-English-speaking countries have reshaped their higher education system to attract more international students. Finland is one of the non-native-English-speaking countries having instituted a change in international student recruitment policy. This study seeks to improve the understanding of the experiences of international students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
6
18
0
Order By: Relevance
“…We have reported that the non-native IUDSs face a language barrier that is even greater while studying a clinically oriented subject such as dentistry in Bangladesh. The data support previously published findings on non-native international students enrolled in universities from non-native-English-speaking countries such as Finland and China [18,35]. Although, their educational infrastructure and pattern are traditionally more established for hosting non-native international students.…”
Section: Strengths and Limitationssupporting
confidence: 88%
“…We have reported that the non-native IUDSs face a language barrier that is even greater while studying a clinically oriented subject such as dentistry in Bangladesh. The data support previously published findings on non-native international students enrolled in universities from non-native-English-speaking countries such as Finland and China [18,35]. Although, their educational infrastructure and pattern are traditionally more established for hosting non-native international students.…”
Section: Strengths and Limitationssupporting
confidence: 88%
“…This new regulation may enable foreign students to be an important source of potential skilled workers, as emphasized by Conception B students. This result echoes Calikoglu's [41] findings that international students not only encounter social, academic, financial, and psychological challenges, but also have concerns about their future career and employability outcomes [42][43][44].…”
Section: Discussionsupporting
confidence: 75%
“…A significant change in a student’s life is the transition from living with family to living away from their social network of family, friends, and neighbors in a non-native foreign country [ 3 , 16 , 18 ]. Adapting to a new environment and the absence of familiar surroundings tend to affect students’ mood and stress levels [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research shows that students who received full intellectual interaction did not suffer from depression in contrast to those with poor academic interaction. In most studies, one of the most critical hurdles for a non-native international students studying healthcare is the inability to communicate [ 18 , 34 ]; the adaptation to the host country’s language. This affects the social interaction with other students and generates a communication gap between the institution and hostel (accommodation) administration who speaks only the host native language [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation